2018
DOI: 10.1038/s41419-018-0736-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and integrative genomic analysis of a panel of newly established penile cancer cell lines

Abstract: Cell line models are essential tools to study the molecular mechanisms underlying tumor initiation and progression. There are limited treatment options for penile squamous cell carcinoma (PSCC), accounting for 1–2% of male tumors in developing countries, and limited progress in preclinical research in PSCC due to lacking available models with identified genomic characteristics. Here, biological and molecular characteristics and whole-genomic alterations were analyzed in a panel of PSCC cell lines newly establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 47 publications
4
33
0
1
Order By: Relevance
“…We also identified novel genes, such as CASP8 (caspase 8; frequency: 4/30), FLG (filaggrin; frequency: 3/30), SLITRK2 (SLIT and NTRK‐like family member 2; frequency: 3/30), CCDC168 (coiled‐coil domain containing 168; frequency: 3/30), TRRAP (transformation/transcription domain‐associated protein; frequency: 3/30) and TTN (titin; frequency: 3/30). Among the 11 frequently mutated genes identified in our study, alterations in TP53 , HRAS , NOTCH1 , PIK3CA and TTN were also frequently observed in the cell lines derived from Chinese penile cancer patients . On the other side, of the critical genes with functional mutations identified by Zhou et al .…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…We also identified novel genes, such as CASP8 (caspase 8; frequency: 4/30), FLG (filaggrin; frequency: 3/30), SLITRK2 (SLIT and NTRK‐like family member 2; frequency: 3/30), CCDC168 (coiled‐coil domain containing 168; frequency: 3/30), TRRAP (transformation/transcription domain‐associated protein; frequency: 3/30) and TTN (titin; frequency: 3/30). Among the 11 frequently mutated genes identified in our study, alterations in TP53 , HRAS , NOTCH1 , PIK3CA and TTN were also frequently observed in the cell lines derived from Chinese penile cancer patients . On the other side, of the critical genes with functional mutations identified by Zhou et al .…”
Section: Discussionsupporting
confidence: 71%
“…On the other side, of the critical genes with functional mutations identified by Zhou et al . in the panel of PSCC cell lines, 10 were found to be altered in our sample too. Additionally, we also observed many less frequent alterations, which often were confounded by random passenger events.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…PSCC cell lines (Penl1, Penl2, and 149RCa) were established in our laboratory. [28][29][30] HaCaT and 293T cells were obtained from the CAS Type Culture Collection of the Chinese Academy of Sciences (Shanghai, China). All cell lines were maintained in Dulbecco's modified Eagle medium supplemented with 10% fetal bovine serum (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Cell Lines and Establishment Of Stable Cell Linesmentioning
confidence: 99%